An extended thomas-fermi model with clustering in nuclei - Nooraihan Abdullah (Institute of Engineering Mathematics, 2016)
The scope of the study is quite wide. The large number of nuclides whose description is important in the nucleosynthesis process calls for a global microscopic theory. Its aim is to describe nuclear properties globally, that is, from helium to superheavy beyond uranium, and to the drip lines relevant to nucleosynthesis. We shall be concerned not only with stable nuclei but also which lie near or beyond the neutron and proton drip lines. This will take care of the extremely short-lived nuclei. This study covers 2149 nuclei with similar to those explored by Audi et al. (Audi, Wapstra, & Thibault, 2003).